PROBLEMS OF EDUCATION FOR SCHEDULED CASTES IN RAJASTHAN - BAIRWA, SITA RAM (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2021)
The Scheduled Castes (SCs) is a group of historically-disadvantaged people recognised by the Constitution of India or the people who are placed at the bottom of the traditional caste system. People of this group in the history performed unclean occupations of the society. As per the recommendation of the Government of Independent India, the President of India in October 1950 included a number of castes in the list of Scheduled Castes following the provisions mentioned under Article 341 (SC) of Constitution of India. The article provides rights to enjoy the social welfare schemes of the government and be a part of the development of the nation to the people who are the member of this category. The Constitution (Scheduled Castes) Order, 1950 lists 1,108 castes across 25 states in its First Schedule and as per the latest amendment in 2008, the list included 1208 scheduled castes across India. The Scheduled Castes of India are put under the reserved categories following the guidelines of the Indian Constitution. The reservation policy became an integral part of the Indian Constitution by the efforts made by Bhimrao Ambedkar, who fought for the rights of the oppressed and depressed classes. Provisions for Scheduled Castes mentioned Under Part XVI-Special Provisions Relating to Certain Classes in the Constitution of India.